EP361 Evolving and validating tool for capacity building of the existing health services staff for VIA and VILI based cervical cancer screening. (1st November 2019) - Mishra, GA; Shylasree, T; Noronha, S; Pramesh, C; Pimple, S; Kulkarni, V; Shaikh, H
Abstract : Introduction/Background: Cervical cancer is the second most common cancer among Indian women. The government is now committed to control common cancers. The objectives are to develop and validate video based training tool for capacity building of existing health services staff in cancer awareness and screening activities, to reduce the expert time involved in the training and to reduce the duration of training. Methodology: Video based tutorials were prepared in ten modules and three languages by TMH in co-ordination with IIT, Mumbai. The health services staff were invited for the training. The training which was for 12 weeks using standard methods was now planned for two weeks using the new technology. Practical demonstration and micro-teaching of health awareness activities, preparation of dilute acetic acid, lugol's iodine, inserting speculums, performing VIA and VILI, identifying lesions, disinfection and sterilization procedures were combined with video based theory and demonstrations. The tablets pre-loaded with the video based tutorials were retained with the trainees during the training period. Results: The fifty trainees were evaluated with theory and practical evaluation. Majority scored well in the theory exams. Out of twenty marks allocated for practical evaluation 49 (98%) scored above 10 marks. All trainees found the training to be very informative, easy to understand and felt confident to deliver cancer awareness talk and to perform VIA and VILI based screening. Conclusion: The outcome of roll out of the cancer control programme will depend on the quality of training imparted to the health services staff. A real-world issue is relieving the health services staff for longer duration for training and the availability of expert time for training. The preparation and validation of these indigenously prepared video based tutorials has opened new avenue by which the vast majority of the health services staff can be trained in relatively shorter duration. Disclosure: Funding Support for preparation of videos was through TMH-IIT Collaborative projects through Tata Trusts and for testing the videos through TMH Intramural funds.